Effects of Metabolic Factors on Left Ventricular Diastolic Function in Patients With Obstructive Sleep Apnea [Corrigendum] - Zhou YF; Chen SH; Wang WD; Chen JL; Cai PY; Li MM; Lin YL; Li WQ; Huang DH; Li J; Li YT; Lin HL (Nature and Science of Sleep)
Zhou YF, Chen SH, Wang WD, et al. Nat Sci Sleep. 2025;17:43—53. Page 43, Abstract, Patients and Methods section, line 1, the text “478 patients” should read “465 patients”. Page 44, Materials and Methods, Study Participants section, line 2, the text “In total, 478” should read “In total, 465”. Page 44, Materials and Methods, Sample Size Determination section, line 3, the text “478 patients” should read “465 patients”. Page 45, Results, Description of the Study Population section, line 1, the text “478 patients” should read “465 patients”. Page 46, Table 1, Before Matching column for MS and non-MS is incorrect for the Gender (Male/Female) row, the text “220 (80.00) /55 (20.00)” and “147 (72.40) /56 (27.60)” should read “212 (79.40 /55 (20.60)” and “143 (72.20) /55 (27.80)”, respectively. The correct Table 1 is as follows.